Plasma and kidney angiotensin II levels and renal functional responses to AT(1) receptor blockade in hypertensive Ren-2 transgenic rats - Kopkan, Libor; Kramer, Herbert J; Husková, Zuzana; Vanourková, Zdenka; Bäcker, Angela; Bader, Michael; Ganten, Detlev; Cervenka, Ludek (Journal of hypertension, 2004)
OBJECTIVE: The first aim of the present study was to assess plasma and kidney angiotensin II (ANG II) levels and renal cortical ANG II receptor subtype 1A (AT1A) mRNA expression in hypertensive Ren-2 transgenic rats (TGR) and in normotensive Hannover Sprague-Dawley (HanSD) rats. The second aim was to investigate potential differences between TGR and HanSD in blood pressure (BP) and renal functional responses to either intravenous (i.v.), i.e. systemic, or intrarenal (i.r.) AT1 receptor blockade with candesartan. METHODS: Rats were anesthetized and prepared for clearance experiments. In series 1, ANG II concentrations were assayed by radioimmunoassay and renal cortical AT1A mRNA expression by semiquantitative reverse transcriptase-polyacrylamide gel electrophoresis. In series 2, BP and renal functional responses were evaluated after either i.v. or i.r. bolus administration of candesartan. RESULTS: Plasma and kidney ANG II levels were significantly lower in TGR than in HanSD (39 +/- 5 versus 107 +/- 19 fmol/ml and 251 +/- 41 versus 571 +/- 95 fmol/g, respectively, P < 0.05). Renal AT1A mRNA expression was not different between TGR and HanSD. Intravenous candesartan caused comparable decreases in BP in TGR and HanSD and did not change renal plasma flow (RPF) or absolute and fractional sodium excretion in HanSD. In contrast, i.v. candesartan significantly increased RPF (+27 +/- 6%, P < 0.05) and absolute and fractional sodium excretion (+49 +/- 10 and + 42 +/- 9%, respectively P < 0.05) in TGR without changing glomerular filtration rate (GFR). Acute i.r. candesartan increased RPF by +36 +/- 6% (P < 0.05) in TGR but not in HanSD with a greater rise in absolute and fractional sodium excretion in TGR (+124 +/-8 and 97 +/- 9%, respectively) than in HanSD (+81 +/- 9 and +69 +/- 8%, respectively) (P < 0.05). CONCLUSIONS: The enhanced responses of RPF and sodium excretion to AT1 receptor blockade in TGR suggest that renal hemodynamics and sodium excretion in TGR are under strong ANG II influence. The compromised ability of the kidney to respond to BP elevations by appropriate increases in sodium excretion may contribute to the maintenance of high BP in TGR. Thus, the present findings provide new insights into the pathophysiology of hypertension in this model.
Keywords: Renal Plasma Flow; Sodium; messenger RNA; Hypertension; Benzimidazoles; Tetrazoles; geneticky modifikovaná zvířata; Glomerular Filtration Rate; Angiotensin II; tetrazoly; angiotensin II; krysa rodu Rattus; Antihypertensive Agents; bifenylové sloučeniny; Biphenyl Compounds; zvířata; hodnoty glomerulární filtrace; benzimidazoly; receptor angiotensinu typ 1; RNA, Messenger; Animals, Genetically Modified; potkani Sprague-Dawley; renální průtok plazmy; hypertenze; sodík; Angiotensin Receptor Antagonists; vyšetření funkce ledvin; Rats; Rats, Sprague-Dawley; Animals; antihypertenziva; Receptor, Angiotensin, Type 1; antagonisté receptorů pro angiotenzin; Kidney Function Tests